Kualiti Kehidupan Kerja Di Kalangan Ahli Kesatuan Sekerja Syarikat Telekom Malaysia Berhad Alor Setar Kedah Darul Aman - Mohd Nazri, Zakaria (2000)
The objective of this study is to examine the relationship of the quality of work life factor to the union members. The drastic changes in business environment in the new millenium have influenced many organizations, which in turns change quality of work life of workers. Motivation theories such as Maslow’s Hierarchical Needs Theory, Theory X and Y, Hygiene Theory and MC Clelland Theory have been studied and applied in the efforts to understand workers’ need. Management concepts such as Management by Objectives (MBO), Employee Recognition Programs, Employee Involvement Program and Quality Circle were also considered. The review of the quality of work life literature is based on Walton (1973) multidimensional 8 factors approach. Data were collected through questionnaire given to 127 randomly chosen member union workers of various departments at Syarikat Telekom Malaysia Bhd Alor Star Kedah. Statistical Package for Social Science Ver. 10.0 (SPSS) was used for data analysis. Descriptive analysis was done to obtain the mean, standard deviation, range, frequency and percentage for demographic and quality of work life factors. In order to examine the relationship, inferential statistics were applied to get the Pearson Correlation, Factor Analysis and Multiple Regression was used. The findings through the factor analysis, it is found that only 7 factors showed the relationship to one another and influenced to the union members. Only 2 factors were found dominant to the workers which is social integration in the work organization and rules in the work organization.